Uvaol Prevents Group B Streptococcus-Induced Trophoblast Cells Inflammation and Possible Endothelial Dysfunction - Silva, Ana Lucia Mendes; Silva, Elaine Cristina Oliveira; Botelho, Rayane Martins; Tenorio, Liliane Patricia Gonçalves; Marques, Aldilane Lays Xavier; Rodrigues, Ingredy Brunele Albuquerque Costa; Almeida, Larissa Iolanda Moreira; Sousa, Ashelley Kettyllem Alves; Pires, Keyla Silva Nobre; Tanabe, Ithallo Sathio Bessoni; Allard, Marie-Julie; Sébire, Guillaume; et al. (Frontiers in Physiology, 2021)
Group B Streptococcus (GBS) infection during pregnancy is involved in maternal sepsis, chorioamnionitis, prematurity, fetal infection, neonatal sepsis, and neurodevelopmental alterations. The GBS-induced chorioamnionitis leads to a plethora of immune and trophoblast cells alterations that could influence endothelial cells to respond differently to angiogenic mediators and alter placental vascular structure and function in pregnant women. In this context, preventive measures are needed to reduce such dysfunctions. As such, we evaluated the effects of a non-lethal exposure to inactivated GBS on trophoblast cells and chorionic villi explants, and if the treatment with uvaol would mitigate these effects. The concentration of 106 CFU of GBS was chosen since it was unable to reduce HTR-8/SVneo cell line nor term chorionic villi explant viability. Raman spectroscopy of trophoblast cells showed significant alterations in their biochemical signature, mostly reverted by uvaol. GBS exposure increased HTR-8/SVneo cells IL-1β and IFN-γ production, phagocytosis, oxidative stress, and decreased trophoblast cell migration. Ea.hy926 endothelial cell line produced angiopoietin-2, CXCL-8, EGF, FGF-b, IL-6, PlGF, sPECAM-1, and VEGF in culture. When co-cultured in invasion assay with HTR-8/SVneo trophoblast cells, increased production of angiopoietin-2, CXCL-8, FGF-b, and VEGF, while reduced sPECAM-1 and IL-6. GBS exposure led to increased CXCL-8 and IL-6 production both prevented by uvaol. Chorionic villi explants followed the same patterns of production when exposed to GBS and response to uvaol treatment as well. These findings demonstrate that even a non-lethal concentration of GBS causes placental inflammation and oxidative stress, reduces trophoblast invasion of endothelial cells, and increases CXCL-8 and IL-6, key factors that participate in vascular dysregulation observed in several diseases. Furthermore, uvaol treatment prevented most of the GBS-provoked changes. Hence, uvaol could prevent the harmful effects of GBS infection for both mother and fetus.